Memotret Praktik Pengurusan Izin Poligami di Pengadilan Agama Kelas 1.A - Dahlia Haliah Ma'u; Wagiyem Wagiyem (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2021)
This research addressed the permit application for polygamy at a religious court (A Case Study at the Religious Court of Class 1-A Pontianak). The research aimed to analyze the following three aspects: the rule, procedure, and verdict process of the permit application for polygamy at the Religious Court of Class 1-A Pontianak. The data of this qualitative research were obtained from the research field. Then the data were narrated and analyzed through methodological steps and ended with a conclusion. The findings showed that, first, the rule of the permit application for polygamy is based on normative rule of legislations in Indonesia and relevant standard operating procedure. Second, the permit application process for polygamy begins with the submission of the application along with required attachments; and third, the verdict of polygamy permission is made according to the steps of trial and mediation. Based on the prosecution presenting parties at different times except for applicant and respondent, the judge makes a verdict to accept or reject the permit application for polygamy.